Experimental Investigation on Organic Matter Orientation Characteristics of Terrestrial and Marine Shale in China - Dunqing Liu; Hongkui Ge; Yinhao Shen; Kui Zhang (Geofluids)
As an essential component in shale, OM (organic matter) grains and their arrangements may play essential roles in affecting the anisotropy of the reservoir. However, OM grains are commonly treated as an evenly distributed isotropic medium in current studies, and few works have been done to investigate their detailed arrangement characteristics. In this study, terrestrial and marine shale samples were collected from three different shale plays in China, and the arrangement characteristics of OM grains in each sample were investigated by SEM (scanning electron microscope) image analysis. The results indicate that OM grains in shale are not evenly distributed in isotropic medium, and their directional alignment is pervasive in both marine and terrestrial shale. OM grains in shale tend to subparallel to the bedding section, and their orientation degree and controlling factors differ among different shales. OM grains in samples from terrestrial C-7(Chang-7 Formation) exhibit the strongest directionality in their arrangement, and OM grains in samples from marine LMX (Longmaxi Formation) shale in the Fuling area also exhibit strong directional alignment. While in samples from marine LMX shale in the Baojing area, their directional alignment is much weaker. Shales with high clay content, high TOC (total organic carbon), low thermal maturity, and flat reservoir structure get more OM grains parallel to the bedding section. The biogenetic texture of graptolite in marine LMX shale is the dominating factor leading to the strong directional alignment of the OM grains. However, syncline structure may disorganize the preformed directional alignment and weaken the directionality of the OM grains, which results in the OM arrangement difference between LMX samples from Fuling and Baojing. While the compaction of the layered clay particles is the dominating mechanism leading to the strong directional alignment of the OM grains in terrestrial shale samples from C-7.